Development of binary and ternary titanium alloys for dental implants. Issue 11 (November 2017) - Cordeiro, Jairo M.; Beline, Thamara; Ribeiro, Ana Lúcia R.; Rangel, Elidiane C.; da Cruz, Nilson C.; Landers, Richard; Faverani, Leonardo P.; Vaz, Luís Geraldo; Fais, Laiza M.G.; Vicente, Fabio B.; Grandini, Carlos R.; Mathew, Mathew T.; et al.
Graphical abstract: Highlights: Binary and ternary Ti alloys were developed. Ti–Zr alloys exhibited enhanced hardness and electrochemical stability. Ti–Nb–Zr alloys presented an elastic modulus closer to that of bone. The experimental alloys were not detrimental to albumin adsorption. The experimental alloys may be considered a suitable candidate for dental implants. Abstract: Objective: The aim of this study was to develop binary and ternary titanium (Ti) alloys containing zirconium (Zr) and niobium (Nb) and to characterize them in terms of microstructural, mechanical, chemical, electrochemical, and biological properties. Methods: The experimental alloys — (in wt%) Ti–5Zr, Ti–10Zr, Ti–35Nb–5Zr, and Ti–35Nb–10Zr — were fabricated from pure metals. Commercially pure titanium (cpTi) and Ti–6Al–4V were used as controls. Microstructural analysis was performed by means of X-ray diffraction and scanning electron microscopy. Vickers microhardness, elastic modulus, dispersive energy spectroscopy, X-ray excited photoelectron spectroscopy, atomic force microscopy, surface roughness, and surface free energy were evaluated. The electrochemical behavior analysis was conducted in a body fluid solution (pH 7.4). The albumin adsorption was measured by the bicinchoninic acid method. Data were evaluated through one-way ANOVA and the Tukey test ( α  = 0.05). Results: The alloying elements proved to modify the alloy microstructure and to enhance the mechanical properties, improving the hardness and decreasing the elastic modulus of the binary and ternary alloys, respectively. Ti–Zr alloys displayed greater electrochemical stability relative to that of controls, presenting higher polarization resistance and lower capacitance. The experimental alloys were not detrimental to albumin adsorption. Significance: The experimental alloys are suitable options for dental implant manufacturing, particularly the binary system, which showed a better combination of mechanical and electrochemical properties without the presence of toxic elements.